Ragam Hias Rumah Soraja di Desa Binaga Karaeng Kecamatan Lembang Kabupaten Pinrang - Saha, Riska; AS, Zulkarnain (TIMPALAJA : Architecture Student Journals, 2020)
Abstrak_Rumah orang Bugis dapat dibedakan berdasarkan status sosial orang yang menempatinya. Daerah Pinrang dikenal istilah saoraja (istana) dan bola (rumah). Berbagai macam motif rumah adat soraja yaitu symbol-simbol ragam dan makna tertentu yang bersifat simbolik sebagai representasi perasaan, pikiran, atau juga paradigma hidup masyarakat Bugis, seperti motif tumbuh-tumbuhan (flora), yaitu motif hias bunga parenreng (sulur suluran), motif hias bunga daun, motif belo-belo tellongeng (jendela), motif hias belo-belo renring (dinding), motif hias belo-belo cappa pattolo (ujung balok), motif hias belo-belo sudu’ (hiasan sudut), motif hias rapang daung kolu (sawi). Motif binatang (fauna) seperti motif hias kepala kerbau, ayam (manuk), dan ular naga. Penelitian ini menggunakan metode kuantitatif untuk mengenali dan memahami bentuk bentk arsitektural dan makna yang terdapat pada Rumah Adat Saoraja di Desa Binanga Karaeng Kecamatan Lembang Kabupaten Pinrang. Kata kunci: Bugis; Pinrang; Soraja; Ragam Hias; Simbol Ragam; Motif. Abstract_ Bugis houses can be distinguished based on the social status of the people who occupy them. Pinrang area known as Saoraja (palace) and bola (home). Various kinds of traditional Soraja house motifs are symbolic variants and specific symbolic meanings as a representation of feelings, thoughts, or also the paradigms of the Bugis community life, such as plant motifs (flora), namely decorating themes of parenting flowers (sulursuluran), decorative motifs of flowers leaves, tellongeng belo-belo motif (window), renring being (wall) ornamental motif, cappa pattolo belo-ornament motif (beam end), belo-belo sudu ’decorative motif (corner decoration), ornamental motifs of rapang daung kolu (mustard greens). Animal motif (fauna) such as buffalo head ornamental motifs, chickens (manuk), and nag snakes. This study uses quantitative methods to recognize and understand the architectural forms and meanings found in the Saoraja Traditional House in Binanga Karaeng Village, Lembang District, Pinrang Regency. Keywords : Bugis; Pinrang; Soraja; Ornamental Variety; Symbol Variety; Motifs. Bugis houses can be distinguished based on the social status of the people who occupy them. Pinrang area known as Saoraja (palace) and bola (home). Various kinds of traditional Soraja house motifs are symbolic variants and specific symbolic meanings as a representation of feelings, thoughts, or also the paradigms of the Bugis community life, such as plant motifs (flora), namely decorating themes of parenting flowers (sulursuluran), decorative motifs of flowers leaves, tellongeng belo-belo motif (window), renring being (wall) ornamental motif, cappa pattolo belo-ornament motif (beam end), belo-belo sudu ’decorative motif (corner decoration), ornamental motifs of rapang daung kolu (mustard greens). Animal motif (fauna) such as buffalo head ornamental motifs, chickens (manuk), and nag snakes. This study uses quantitative methods to recognize and understand the architectural forms and meanings found in the Saoraja Traditional House in Binanga Karaeng Village, Lembang District, Pinrang Regency. Keywords : Bugis; Pinrang; Soraja; Ornamental Variety; Symbol Variety; Motifs.